Customer-centricity : the new path to product innovation and profitability - Valls, Josep-Francesc (Cambridge Scholars Publishing, 2018)
The empowered customer is here to stay. With a low tolerance for subpar experiences, they have no qualms in switching brands if disappointed, and expect companies to provide offers that are personally relevant to them. This realisation has led enterprises to revamp their business strategies to meet the high expectations of these savvy and hyper-connected consumers. This requires a 360 degree customer-centric approach--fuelled by big data--that attempts to understand customer problems and deliver timely solutions. The ability to use customer journey mapping and real-time analytics to unlock act.